The Living Stream Yeats Annual No. 18 - Gould, Warwick (Yeats Annual, 2013)
"Yeats Annual No. 18 is another special issue in this renowned research-level series offering a tribute to the pioneering Yeats scholar, A. Norman Jeffares. Memories of the man are shared by Seamus Heaney, Christopher Rush and Colin Smythe, who compiles a bibliography of Jeffares's work. Terence Brown, Neil Corcoran, Warwick Gould, Joseph M. Hassett, Phillip L. Marcus, Ann Saddlemyer, Ronald Schuchard, Deirdre Toomey and Helen Vendler offer essays on such topics as Yeats and the Colours of Poetry, Yeats's Shakespeare, Yeats and Seamus Heaney, Lacrimae Rerum and Tragic Joy, Raftery's work on Yeats's Thoor Ballylee, Edmund Dulac's portrait of Mrs George Yeats, The Tower as an anti-Modernist monument, with close studies of 'Vacillation', 'Her Triumph', and 'The Cold Heaven'. Throughout, the essays are inflected with memories of Jeffares and his critical methods. The volume is rounded with further essays on A Vision by Neil Mann and Matthew de Forrest, while reviews of recent editions and studies are provided by Matthew Campbell, Wayne K. Chapman, Sandra Clark, Denis Donoghue, Nicholas Grene, Joseph M. Hassett, and K.P.S. Jochum. Yeats Annual is published by Open Book Publishers in association with the Institute of English Studies, University of London."